2001
DOI: 10.1097/00005537-200110000-00031
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor Receptor 2 (VEGFR2) Expression in Squamous Cell Carcinomas of the Head and Neck

Abstract: Analysis of frozen sections by immunohistochemistry showed that in 90% of tumor specimens VEGFR2-positive cells were found which were associated with vascular endothelium. VEGFR2 was also expressed on tumor cells and vessels, which was confirmed by double immunolabeling of tumor cells with an a-cytokeratin mAb. Furthermore, 2 (JPPA, SCC9) of 4 HNSCC cultured tumor cell lines revealed positive VEGFR2 immunoreactivity. Synthesis of VEGFR2 mRNA on all 4 HNSCC cultured tumor cell lines (JPPA, SCC9, SCC25, and LFFR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 42 publications
(48 reference statements)
1
35
1
Order By: Relevance
“…before by Neuchrist et al (2001). Taken together, it seems likely that two overlapping systems are involved in the tumorigenicity and tumour angiogenesis with autocrine/paracrine loops using VEGF and VEGFR2.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…before by Neuchrist et al (2001). Taken together, it seems likely that two overlapping systems are involved in the tumorigenicity and tumour angiogenesis with autocrine/paracrine loops using VEGF and VEGFR2.…”
Section: Discussionmentioning
confidence: 96%
“…The key VEGF receptor present on endothelial cells is VEGFR2. In addition, the presence of VEGFR2 has been reported on tumour cells themselves, particularly in head and neck cancer (Neuchrist et al, 2001). For this reason, we analysed VEGFR2 expression both on endothelial cells and on tumour cells.…”
mentioning
confidence: 99%
“…Recently, it has been reported that VEGF and VEGFR-2 were coexpressed in various types of solid tumors [6, 19, 20]. These data have suggested the presence of an autocrine growth pathway involving VEGF and VEGFR-2.…”
Section: Discussionmentioning
confidence: 99%
“…25 Our results also implicate the significance of VEGF-C and VEGFR3 in tumor-dependent angiogenesis, which in turn is closely associated with tumor growth and metastases. 4 In HNSCCs, evidence of angiogenesis has been provided (ie, increased microvessel density, 26 upregulated VEGF, 7,8,27 VEGFR1, 28 VEGFR2, 13,29 and bFGF). 30,31 Nobody has previously featured details about lymph angiogenesis in HNSCC, tumors with a predilection for locoregional lymphatic metastasization.…”
Section: Vegf-c Expression In Hnsccmentioning
confidence: 99%